Diabetes in relation to Barrett's esophagus and adenocarcinomas of the esophagus: A pooled study from the International Barrett's and Esophageal Adenocarcinoma Consortium. Issue 23 (6th September 2019) - Petrick, Jessica L.; Li, Nan; Anderson, Lesley A.; Bernstein, Leslie; Corley, Douglas A.; El Serag, Hashem B.; Hardikar, Sheetal; Liao, Linda M.; Liu, Geoffrey; Murray, Liam J.; Rubenstein, Joel H.; Schneider, Jennifer L.; et al.
Abstract : Background: Diabetes is positively associated with various cancers, but its relationship with tumors of the esophagus/esophagogastric junction remains unclear. Methods: Data were harmonized across 13 studies in the International Barrett's and Esophageal Adenocarcinoma Consortium, comprising 2309 esophageal adenocarcinoma (EA) cases, 1938 esophagogastric junction adenocarcinoma (EGJA) cases, 1728 Barrett's esophagus (BE) cases, and 16, 354 controls. Logistic regression was used to estimate study‐specific odds ratios (ORs) and 95% CIs for self‐reported diabetes in association with EA, EGJA, and BE. Adjusted ORs were then combined using random‐effects meta‐analysis. Results: Diabetes was associated with a 34% increased risk of EA (OR, 1.34; 95% CI, 1.00‐1.80; I 2  = 48.8% [where 0% indicates no heterogeneity, and larger values indicate increasing heterogeneity between studies]), 27% for EGJA (OR, 1.27; 95% CI, 1.05‐1.55; I 2  = 0.0%), and 30% for EA/EGJA combined (OR, 1.30; 95% CI, 1.06‐1.58; I 2  = 34.9%). Regurgitation symptoms modified the diabetes‐EA/EGJA association ( P for interaction = .04) with a 63% increased risk among participants with regurgitation (OR, 1.63; 95% CI, 1.19‐2.22), but not among those without regurgitation (OR, 1.03; 95% CI, 0.74‐1.43). No consistent association was found between diabetes and BE. Conclusions: Diabetes was associated with increased EA and EGJA risk, which was confined to individuals with regurgitation symptoms. Lack of an association between diabetes and BE suggests that diabetes may influence progression of BE to cancer. Abstract : Diabetes has a positive association with various cancers, but its relationship to tumors of the esophagus and the esophagogastric junction remains unclear. In this study, we identified a positive association between diabetes and esophageal and esophagogastric junction adenocarcinomas, but not Barrett's esophagus, suggesting that diabetes may be acting later in the carcinogenesic pathway.